An mTORC1/2 kinase inhibitor enhances the cytotoxicity of gemtuzumab ozogamicin by activation of lysosomal function. (November 2018) - Maimaitili, Yimamu; Inase, Aki; Miyata, Yoshiharu; Kitao, Akihito; Mizutani, Yu; Kakiuchi, Seiji; Shimono, Yohei; Saito, Yasuyuki; Sonoki, Takashi; Minami, Hironobu; Matsuoka, Hiroshi
Highlights: Low-dose mTORC1/2 kinase inhibitor, PP242, activates lysosomal function. PP242 may increase free calicheamicin by improving the efficiency of linker hydrolysis. PP242 suppresses GO-induced Chk1 activation and proceeds cell cycle. PP242 enhances the cytotoxic effect of GO in different leukemia cells. Abstract: Gemtuzumab ozogamicin (GO), the first antibody-drug conjugate (ADC), has attracted the interest of hematologists because more than 90% of acute myeloid leukemia (AML) blasts express its target, CD33. Although GO and subsequently developed ADCs depend on lysosomes for activation, lysosome number and activity in tumor cells has not been well elucidated. In this study, we investigated whether an mTORC1/2 kinase inhibitor, PP242, which was reported to activate lysosomal function, potentiates the cytotoxicity of GO in AML cells. Eight AML cell lines (U937, THP-1, SKM-1, SKK-1, SKNO-1, HL-60, MARIMO and KO52) were treated with GO and PP242. The cytotoxic effect of GO was enhanced by concurrent treatment with a non-cytotoxic concentration (500 nM) of PP242 in most cell lines, except MARIMO and KO52 cells. We then used LysoTracker to label acidic lysosomes in U937, THP-1, SKM-1, MARIMO and KO52 cells. LysoTracker fluorescence was dramatically increased by treatment with PP242 in U937, THP-1 and SKM-1 cells, and the intensified fluorescence was retained with PP242 + GO. In contrast, PP242 did not induce a significant increase in fluorescence in MARIMO cells, consistent with the lack of combinatory cytotoxicity. LysoTracker fluorescence was also increased by PP242 in KO52 cells, which have been reported to strongly express multidrug resistance (MDR). Further, PP242 suppressed GO-induced Chk1 activation and G2/M cell cycle arrest, which in turn triggered cell cycle promotion and cell death. These results indicate that inhibition of mTORC1/2 kinase by PP242 enhanced the cytotoxicity of GO by increasing lysosomal compartments and promoting the cell cycle via suppression of GO-induced Chk1 activation. This combination may represent an attractive new therapeutic strategy for the treatment of leukemia.